2009
DOI: 10.1369/jhc.2009.952275
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Neural Stem Cells and Generation of New Neurons in 6-OHDA–lesioned Rats by Intracerebroventricular Infusion of Liver Growth Factor

Abstract: S U M M A R Y Neural stem cells with self-renewal and multilineage potential persist in the subventricular zone of the adult mammalian forebrain. These cells remain relatively quiescent but, under certain conditions, can be stimulated, giving rise to new neurons. Liver growth factor (LGF) is a mitogen for liver cells that shows biological activity in extrahepatic sites and is useful for neuroregenerative therapies. The aim of this study was to investigate the potential neurogenic activity of LGF in the 6-hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
34
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 73 publications
5
34
0
1
Order By: Relevance
“…LGF was also able to increase endothelial cell number, as previously described in intraparenquimal cerebral vessels from rats treated with LGF (35). All these data suggest that LGF acts as mitogen for vascular cells, and it is able to normalize the imbalance between decreased cell number-excessive ECM production in the vascular wall.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…LGF was also able to increase endothelial cell number, as previously described in intraparenquimal cerebral vessels from rats treated with LGF (35). All these data suggest that LGF acts as mitogen for vascular cells, and it is able to normalize the imbalance between decreased cell number-excessive ECM production in the vascular wall.…”
Section: Discussionsupporting
confidence: 81%
“…We have previously demonstrated that the excessive ECM deposition by VSMC from SHR is related to a cellular defect in SHR, consisting of defective proliferation, but enhanced cell survival of hypertrophied diploid cells, which keep producing ECM, without normal turnover (7). On the other hand, the regenerative actions of LGF in several biological systems have been linked to its mitogenic effects (26,27,35,52). In our previous study, we also reported that LGF was able to improve the reduced VSMC density and abnormally high ploidy in carotid arteries from SHR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In view of the results obtained in this study, what seems clear is that LGF treatment promotes tissue regeneration, probably by promoting cell proliferation (7,18,39,42) of the lung parenchyma. Maybe the LGF stimulates cellular antioxidant response (8,9) or decreases cellular apoptotic processes (13).…”
Section: Discussionmentioning
confidence: 61%